Styrene and ethylbenzene exposure and type 2 diabetes mellitus: A longitudinal gene–environment interaction study - Linling Yu; Wei Liu; Yongfang Zhang; Qiyou Tan; Jiahao Song; Lieyang Fan; Xiaojie You; Min Zhou; Bin Wang; Weihong Chen (Eco-Environment & Health)
Styrene and ethylbenzene (S/EB) are identified as hazardous air contaminants that raise significant concerns. The association between S/EB exposure and the incidence of type 2 diabetes mellitus (T2DM), and the interaction between genes and environment, remains poorly understood. Our study consisted of 2219 Chinese adults who were part of the Wuhan-Zhuhai cohort. A follow-up assessment was conducted after six years. Exposure to S/EB was quantified by determining the concentrations of urinary biomarkers of exposure to S/EB (UBE-S/EB; urinary phenylglyoxylic acid level plus urinary mandelic acid level). Logistic regression models were constructed to investigate the relations of UBE-S/EB and genetic risk score (GRS) with T2DM prevalence and incidence. The interaction effects of UBE-S/EB and GRS on T2DM were investigated on multiplicative and additive scales. UBE-S/EB was dose-dependently and positively related to T2DM prevalence and incidence. Participants with high levels of UBE-S/EB [relative risk (RR) = 1.930, 95% confidence interval (CI): 1.157–3.309] or GRS (1.943, 1.110–3.462) demonstrated the highest risk of incident T2DM, in comparison to those with low levels of UBE-S/EB or GRS. Significant additive interaction between UBE-S/EB and GRS on T2DM incidence was discovered with relative excess risk due to interaction (95% CI) of 0.178 (0.065–0.292). The RR (95% CI) of T2DM incidence was 2.602 (1.238–6.140) for individuals with high UBE-S/EB and high GRS, compared to those with low UBE-S/EB and low GRS. This study presented the initial evidence that S/EB exposure was significantly related to increased risk of T2DM incidence, and the relationship was interactively aggravated by genetic predisposition.